Dilemma of mandatory vaccination for COVID 19: analysis of constitutional and legal issues under the Sri Lankan Law - Udayanganie, U.A.T. (Faculty of Law, University of Colombo, 2021)
Sri Lankan authorities have suggested that the vaccination card for COVID-19 be made mandatory for citizens above the age of 30 years old, whenever they visit public places from Sept. 15, 2021 onwards. Such policies appear to be effective in convincing some non- vaccinated individuals to get their dosage to ensure community safety. Even so, this raises many complex issues regarding the interplay of competing rights. The key issue is where to draw the line between government's duty to protect the health and community protection and the individual autonomy, bodily integrity and human dignity, particularly when a worldwide pandemic causes millions of deaths and economic devastation. Another crucial point that need to be considered in the current vaccination debate in Sri Lanka is that Covid-19 poses a major public health risk not just to people who are non-vaccinated by choice, but to those who cannot yet get vaccinated, such as children due to irregular and inconsistent supply of vaccines, issues in the process of vaccination prioritization and people who did get vaccinated but develop breakthrough infections. First part of this paper presents a constitutional and legal analysis of the possibility of the country making the vaccination against COVID-19 mandatory. Second part of the paper seeks to reflect debates in other jurisdictions as well where mandatory vaccination is being recommended to tackle the COVID-19 pandemic. Finally, the paper suggests the proportionality approach in designing and implementing such a law or policy and substantiates the argument that a mandatory vaccination would be legal if the government has designed and implemented rational criteria within the explicit parameters that a mandatory vaccination is required and proportionate in the interest of public health and safety and for the protection of the rights and freedoms of the community. The research employs a doctrinal black letter approach by referring to relevant primary and secondary sources.
Keywords: mandatory vaccination; fundamental rights; public interest; constitutionality; legality